Agarose Hydrogel & LLRP As Adjuncts to Remineralization - Neco Lawrence; Hanna Passmore; Ashley Christman, RDH, BS (Elsevier, 2024)
OBJECTIVES: Examine the current efficacy of Agarose Hydrogel & LRAP (Luciene rich Amelogenin proteins) as biomimetic adjuncts to remineralization by mimicking the beginning stages of amelogenesis; creating new tooth structure. METHODS: For this review, the articles used were accessed from the Augusta UniversityDatabase and published within the past 5 years. We excluded meta-analysis and literature reviews. Used the keywords: enamel regeneration, agarose, hydrogel, enamel remineralization. RESULTS: (If applicable) In these studies, teeth were disinfected in a 3% sodium hypochlorite solution and layered with Saline buffered with Phosphate. The teeth were then sliced with different methods, and ultrasonically cleansed. They were then etched with 37% phosphoric acid and stored to mimic constant demineralization. All of the adjuncts were shown to have the ability to replicate Hydroxyapatite crystals and the structure of enamel. The LRAP solution maintained a neutral pH level that protects the phosphate and enables it to stabilize enamel regeneration. After 6 days, the Agarose Hydrogel can regenerate mineralized tissues like sound enamel. After being treated with enamel matrix proteins, after 24 hours, the hydroxyapatite crystals formed prismatic structures with a 5 μm diameter. CONCLUSIONS: Each study indicates that LRAP, Agarose Hydrogel, and Enamel Matrix Proteins could direct enamel regeneration. LRAP is a promising biomolecule for enamel regeneration because of its capacity to affect crystal positioning and form. Comparatively to amelogenesis, Agarose Hydrogel has significantly promising results to replicate sound enamel. The Enamel Matrix Proteins can spontaneously self- assemble into nanosphere structures and attract calcium and phosphate ions like sound enamel. IMPLICATIONS: Long-term clinical trials would be needed to measure risks & potential adverse effects. Restorative work of this nature may be costly with or without private insurance, it may be beneficial to find more cost- effective biomimetic materials.Treatment would happen over multiple days in private practice. Further studies would be needed to examine the limitations of how much enamel can be synthetically produced.